2021
DOI: 10.3390/nu13093231
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Atherogenic Index of Plasma (AIP) for the Risk of Incident Ischemic Heart Disease among Non-Diabetic Koreans

Abstract: The atherogenic index of plasma (AIP), composed of triglycerides and high-density lipoprotein cholesterol, is a novel critical marker for assessing the risk of atherogenicity and cardiometabolic health. We aimed to prospectively study the association between AIP and incident ischemic heart disease (IHD) risk in a large cohort of non-diabetic Korean adults. Data were assessed from 17,944 participants without diabetes from the Health Risk Assessment Study (HERAS) and Korea Health Insurance Review and Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…This study found that low AIP in Korean adult men was favorable for body weight, waist circumference, BMI, fasting blood glucose, HbA1c, and lipid metabolism parameters. Studies by Zhu et al [ 15 ] and Kim [ 34 ], in which AIP levels were divided into quartiles as done in this study, reported that as AIP values increased from the first to fourth quartile, BMI values increased. In particular, the study by Zhu et al found an association between AIP and obesity; when a BMI ≥ 28 kg/m 2 was defined as obesity, higher AIP levels were positively and strongly associated with obesity [ 15 ].…”
Section: Discussionmentioning
confidence: 55%
“…This study found that low AIP in Korean adult men was favorable for body weight, waist circumference, BMI, fasting blood glucose, HbA1c, and lipid metabolism parameters. Studies by Zhu et al [ 15 ] and Kim [ 34 ], in which AIP levels were divided into quartiles as done in this study, reported that as AIP values increased from the first to fourth quartile, BMI values increased. In particular, the study by Zhu et al found an association between AIP and obesity; when a BMI ≥ 28 kg/m 2 was defined as obesity, higher AIP levels were positively and strongly associated with obesity [ 15 ].…”
Section: Discussionmentioning
confidence: 55%
“…The present research is based on the Health Risk Assessment Study (HERAS) and Korea Health Insurance Review and Assessment Service (HIRA) datasets, which aimed to explore and characterize cardiovascular risk factors among Koreans without diabetes [ 14 , 15 ]. The cohort consisted of 20,530 subjects who voluntarily underwent medical examinations at Yonsei University Gangnam Severance Hospital between November 2006 and June 2010 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In combination with related studies predicting prognosis for non-diabetic patients, AIP index is thought to have priority [ 18 , 44 ]. For non-diabetic patients who had previous received PCI therapy upon admission, an assessment of metabolism dysfunction could be useful.…”
Section: Discussionmentioning
confidence: 99%